Economic dispatch solution using bacteria foraging optimization / Mohd Salehudin Samsudin - Samsudin, Mohd Salehudin (2011)
Economic dispatch problem is an optimization problem where objective function is highly non-linear, non-convex, non-differentiable and may have multiple local minima. Therefore, classical optimization method may not converge or get trapped to any local minima. This paper presents a Bacteria Foraging Optimization (BFO) for economic dispatch problem in power system. BFO has been proposed to solve this complex problem and tested on the three unit generation system. The results obtained show that the method is able to provide the solution for economic dispatch problem.